2022
DOI: 10.3390/nano12071042
|View full text |Cite
|
Sign up to set email alerts
|

Selective Catalytic Reduction of NOx over Perovskite-Based Catalysts Using CxHy(Oz), H2 and CO as Reducing Agents—A Review of the Latest Developments

Abstract: Selective catalytic reduction (SCR) is probably the most widespread process for limiting NOx emissions under lean conditions (O2 excess) and, in addition to the currently used NH3 or urea as a reducing agent, many other alternative reductants could be more promising, such as CxHy/CxHyOz, H2 and CO. Different catalysts have been used thus far for NOx abatement from mobile (automotive) and stationary (fossil fuel combustion plants) sources, however, perovskites demand considerable attention, partly due to their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 101 publications
0
6
0
Order By: Relevance
“…The mass spectra of FTMBr (Figure S1D) also confirmed this result. As shown in Figure S1A, the electron gain and loss of FTMBr lay the foundation for redox reactions. This switchable process can be realized by redox stimuli as oxidizing/reducing agents or electrochemical methods. The method of carrying out simple and convenient catalytic oxidation of ferrocene plays an important role in the development of the redox properties of ferrocene.…”
Section: Resultsmentioning
confidence: 99%
“…The mass spectra of FTMBr (Figure S1D) also confirmed this result. As shown in Figure S1A, the electron gain and loss of FTMBr lay the foundation for redox reactions. This switchable process can be realized by redox stimuli as oxidizing/reducing agents or electrochemical methods. The method of carrying out simple and convenient catalytic oxidation of ferrocene plays an important role in the development of the redox properties of ferrocene.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, mixed metal oxides, especially those of the perovskite class (ABO 3 ), combine high thermal and chemical stabilities with the adequate activity of oxidation reactions, while keeping their cost relatively low [42][43][44][45][46]. Perovskites based on the combination of La and Mn in the A and B sites, respectively, are among the most popular materials in the family.…”
Section: Introductionmentioning
confidence: 99%
“…Perovskites based on the combination of La and Mn in the A and B sites, respectively, are among the most popular materials in the family. The partial substitution of La 3+ by Sr 2+ in the perovskite structure (i.e., La 1−x Sr x MnO 3 ) can enhance the redox properties of the material by increasing the oxygen vacancies and the oxidation state of the B cation (Mn), introducing significant changes to their catalytic performance and their thermal stability [42][43][44][45][46][47][48][49]. Especially after the inspiring discovery of Nishihata et al [50] and Tanaka et al [51], who demonstrated the self-regenerative function of noble metal substituted perovskites, a phenomenon that was later called "redox exclusion" [52,53], as well as methods that determine the nanostructure of the perovskite itself, thus improving the surface area and other catalysisrelated properties [54,55], new horizons were opened for the use of perovskites in various environmental- [54,[56][57][58][59] and energy- [55,[60][61][62][63][64] related catalytic processes, which resulted in great success.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For SCR NOx reduction, a variety of catalysts have been studied, including platinum group metals (PGM), perovskite-type oxides, spinel-type oxides, and mixed transition metal oxides [12][13][14][15]. In a low-temperature selective catalytic reduction, low-cost spinels were used [16].…”
Section: Introductionmentioning
confidence: 99%